Impact of wind flow and global warming in the dynamics of prey–predator model - Thirthar, Ashraf Adnan; Jawad, Shireen; Majeed, Salam J.; Nisar, Kottakkaran Sooppy (Results in control and optimization, 2024)
Prey–predator interaction is among the most crucial aspects of ecology. In this paper, the dynamics of a prey–predator system in which the prey and predator populations experience a birth rate reduction due to global warming and the wind flow effect on them are investigated. The system’s well-posedness before presenting findings about the existence of potential equilibrium points is studied. Conditions under which a different number of interior equilibria exist are also derived here. It is very important to know that when the positive equilibrium point is stable, this reflects positively on the ecosystem, its continuity and persistence. The conditions that have been identified are conditions that preserve the ecosystem from extinction when environmental influences such as global warming and wind speed are present. In addition, the local stability study around all equilibrium points and established the transversality criteria for the occurrence of transcritical bifurcations and Hopf bifurcations is conducted. The existence of different equilibrium points numerically by altering the prey’s global warming effect is illustrated , also showcasing the model’s dynamic character from a mathematical perspective. For significant amounts of global warming, its notice that the system exhibits periodic behavior. Thus, ecologists can approximate the parameters necessary to investigate and obtain such crucial findings regarding nonlinear systems with the aid of the current study.